THE INFLUENCE OF ENERGY SAVING PROCESSING UPON BIOLOGICAL SOIL ACTIVITY IN BARLEY SOWINGS - E. P. Denisov; K. E. Denisov; E. V. Podgornov; V. V. Karpets (Зерновое хозяйство России)
In the article the study results of influence of minimum and zero tillage upon biological soil activity compared with conventional one are considered. It’s established that tillage under decrease of soil density and increase of general porosity, especially porosity of autumn aeration is more preferable and advantageous than minimum and zero tillage. Increase of humus content and decrease of nitrate N in an upper layer of the soil have been found under decrease of tillage with straw.  Micro biological analysis showed increase of saprophytic microorganisms during tillage. Their quantity was in 2-3 times more than after minimum and zero tillage. Under zero tillage there was decrease of ammonifying and nitrifying bacteria, but increase of anaerobic cellulose-destroying microorganisms. Barley cultivation under energy saving tillage decreased its productivity on 17,7-22,9% compared with plowing. Fertilizing increased productivity under plowing, under minimum tillage and under zero tillage on 10,8%, on 19,6% and on 19,4% respectively.  Advantage of energy saving tillage under calculation of economic efficiency of barley was shown.